Two Croatian Localities - Leutloff-Grandits, Carolin (Array, 2010)
This contribution examines family life and social security in two settings: one urban and one rural. The paper is both an ethnographic account to the contemporary family life and ethnological interpretation of several sub-topics, such as childcare and elderly care, examined through the concept of social security.